2009
DOI: 10.1158/1078-0432.ccr-09-0479
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-CD44 Interactions in Cancer: Paradoxes and Possibilities

Abstract: Hyaluronan is a prominent component of the micro-environment in most malignant tumors and can be prognostic for tumor progression. Extensive experimental evidence in animal models implicates hyaluronan interactions in tumor growth and metastasis, but it is also evident that a balance of synthesis and turnover by hyaluronidases is critical. CD44, a major hyaluronan receptor, is commonly but not uniformly associated with malignancy, and is frequently used as a marker for cancer stem cells in human carcinomas. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
316
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(321 citation statements)
references
References 75 publications
4
316
0
1
Order By: Relevance
“…This difference could be explained by differences in immuno-histochemical procedures. [47] In the present study, we also found a significant (p = .04) association between high N-cadherin expression and neural invasion as 86.7% of cases that showed neural invasion exhibited high expression of N-cadherin. Kehagias et al also reported similar results in their series of salivary gland tumors as N-cadherin was not expressed in benign neoplasms, but was expressed in half of the malignant ones.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This difference could be explained by differences in immuno-histochemical procedures. [47] In the present study, we also found a significant (p = .04) association between high N-cadherin expression and neural invasion as 86.7% of cases that showed neural invasion exhibited high expression of N-cadherin. Kehagias et al also reported similar results in their series of salivary gland tumors as N-cadherin was not expressed in benign neoplasms, but was expressed in half of the malignant ones.…”
Section: Discussionsupporting
confidence: 78%
“…[46] HA acting through promoting cell adhesion and motility, proliferation, and differentiation. [47] Growth factors and chemokines produced in tumor microenvironment can induce HA production. [48] In the current study, HA was expressed in the proliferating tumor islands and in the surrounding stroma with variable intensity of the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…S1), in which HA is significantly represented. Third and most importantly, HA was shown to be a critical modulator of EMT phenotypes in normal and cancerous epithelial cells, and its abundance in the stromal environment of cancer cells causes their invasion and metastasis (30). Indeed, treatment of cocultures of MSCs and cancer cells with hyaluronidase inhibited MSC-induced LOX (and Twist) expression in BCC MSC (Fig.…”
Section: Hyaluronan-cd44 Interactions Mediate Msc-induced Lox and Twistmentioning
confidence: 95%
“…HA acts through multiple receptors, with CD44 being its major partner in cancer (30). We, therefore, proceeded to explore whether it mediated the actions of MSCs on the LOX-Twist axis.…”
Section: Hyaluronan-cd44 Interactions Mediate Msc-induced Lox and Twistmentioning
confidence: 99%
“…Due to the complexity of CD44 interactions, it has been assigned many functions, including lymphocyte homing, cell adhesion, migration, and proliferation. These functions are important in physiological and pathological processes like wound healing, inflammation, and cancer (1,2).…”
mentioning
confidence: 99%